MAYBE Initial complexity problem: 1: T: (?, 1) f11(a, b, c, d, e, f) -> f11(a - 1, b - 1, c + 1, g, e, f) [ a >= 1 /\ g >= 1 ] (?, 1) f11(a, b, c, d, e, f) -> f11(a - 1, b, c, g, e, f) [ 0 >= g /\ a >= 1 /\ a >= b + 1 ] (?, 1) f21(a, b, c, d, e, f) -> f21(a, b, c, d, e, f) (?, 1) f23(a, b, c, d, e, f) -> f26(a, b, c, d, e, f) (?, 1) f11(a, b, c, d, e, f) -> f21(a, b, c, d, e, f) [ 0 >= a ] (1, 1) f0(a, b, c, d, e, f) -> f11(4, g, 0, d, g, 4) [ g >= 1 ] start location: f0 leaf cost: 0 Repeatedly removing leaves of the complexity graph in problem 1 produces the following problem: 2: T: (?, 1) f11(a, b, c, d, e, f) -> f11(a - 1, b - 1, c + 1, g, e, f) [ a >= 1 /\ g >= 1 ] (?, 1) f11(a, b, c, d, e, f) -> f11(a - 1, b, c, g, e, f) [ 0 >= g /\ a >= 1 /\ a >= b + 1 ] (?, 1) f21(a, b, c, d, e, f) -> f21(a, b, c, d, e, f) (?, 1) f11(a, b, c, d, e, f) -> f21(a, b, c, d, e, f) [ 0 >= a ] (1, 1) f0(a, b, c, d, e, f) -> f11(4, g, 0, d, g, 4) [ g >= 1 ] start location: f0 leaf cost: 1 A polynomial rank function with Pol(f11) = 1 Pol(f21) = 0 Pol(f0) = 1 orients all transitions weakly and the transition f11(a, b, c, d, e, f) -> f21(a, b, c, d, e, f) [ 0 >= a ] strictly and produces the following problem: 3: T: (?, 1) f11(a, b, c, d, e, f) -> f11(a - 1, b - 1, c + 1, g, e, f) [ a >= 1 /\ g >= 1 ] (?, 1) f11(a, b, c, d, e, f) -> f11(a - 1, b, c, g, e, f) [ 0 >= g /\ a >= 1 /\ a >= b + 1 ] (?, 1) f21(a, b, c, d, e, f) -> f21(a, b, c, d, e, f) (1, 1) f11(a, b, c, d, e, f) -> f21(a, b, c, d, e, f) [ 0 >= a ] (1, 1) f0(a, b, c, d, e, f) -> f11(4, g, 0, d, g, 4) [ g >= 1 ] start location: f0 leaf cost: 1 A polynomial rank function with Pol(f11) = V_1 Pol(f21) = V_1 Pol(f0) = 4 orients all transitions weakly and the transitions f11(a, b, c, d, e, f) -> f11(a - 1, b, c, g, e, f) [ 0 >= g /\ a >= 1 /\ a >= b + 1 ] f11(a, b, c, d, e, f) -> f11(a - 1, b - 1, c + 1, g, e, f) [ a >= 1 /\ g >= 1 ] strictly and produces the following problem: 4: T: (4, 1) f11(a, b, c, d, e, f) -> f11(a - 1, b - 1, c + 1, g, e, f) [ a >= 1 /\ g >= 1 ] (4, 1) f11(a, b, c, d, e, f) -> f11(a - 1, b, c, g, e, f) [ 0 >= g /\ a >= 1 /\ a >= b + 1 ] (?, 1) f21(a, b, c, d, e, f) -> f21(a, b, c, d, e, f) (1, 1) f11(a, b, c, d, e, f) -> f21(a, b, c, d, e, f) [ 0 >= a ] (1, 1) f0(a, b, c, d, e, f) -> f11(4, g, 0, d, g, 4) [ g >= 1 ] start location: f0 leaf cost: 1 Applied AI with 'oct' on problem 4 to obtain the following invariants: For symbol f11: -X_6 + 4 >= 0 /\ X_5 - X_6 + 3 >= 0 /\ X_3 - X_6 + 4 >= 0 /\ -X_1 - X_6 + 8 >= 0 /\ X_6 - 4 >= 0 /\ X_5 + X_6 - 5 >= 0 /\ X_3 + X_6 - 4 >= 0 /\ -X_1 + X_6 >= 0 /\ X_5 - 1 >= 0 /\ X_3 + X_5 - 1 >= 0 /\ -X_1 + X_5 + 3 >= 0 /\ -X_1 - X_3 + 4 >= 0 /\ X_3 >= 0 /\ -X_1 + X_3 + 4 >= 0 /\ -X_1 + 4 >= 0 For symbol f21: -X_6 + 4 >= 0 /\ X_5 - X_6 + 3 >= 0 /\ X_3 - X_6 + 4 >= 0 /\ -X_1 - X_6 + 4 >= 0 /\ X_6 - 4 >= 0 /\ X_5 + X_6 - 5 >= 0 /\ X_3 + X_6 - 4 >= 0 /\ -X_1 + X_6 - 4 >= 0 /\ X_5 - 1 >= 0 /\ X_3 + X_5 - 1 >= 0 /\ -X_1 + X_5 - 1 >= 0 /\ -X_1 - X_3 + 4 >= 0 /\ X_3 >= 0 /\ -X_1 + X_3 >= 0 /\ -X_1 >= 0 This yielded the following problem: 5: T: (1, 1) f0(a, b, c, d, e, f) -> f11(4, g, 0, d, g, 4) [ g >= 1 ] (1, 1) f11(a, b, c, d, e, f) -> f21(a, b, c, d, e, f) [ -f + 4 >= 0 /\ e - f + 3 >= 0 /\ c - f + 4 >= 0 /\ -a - f + 8 >= 0 /\ f - 4 >= 0 /\ e + f - 5 >= 0 /\ c + f - 4 >= 0 /\ -a + f >= 0 /\ e - 1 >= 0 /\ c + e - 1 >= 0 /\ -a + e + 3 >= 0 /\ -a - c + 4 >= 0 /\ c >= 0 /\ -a + c + 4 >= 0 /\ -a + 4 >= 0 /\ 0 >= a ] (?, 1) f21(a, b, c, d, e, f) -> f21(a, b, c, d, e, f) [ -f + 4 >= 0 /\ e - f + 3 >= 0 /\ c - f + 4 >= 0 /\ -a - f + 4 >= 0 /\ f - 4 >= 0 /\ e + f - 5 >= 0 /\ c + f - 4 >= 0 /\ -a + f - 4 >= 0 /\ e - 1 >= 0 /\ c + e - 1 >= 0 /\ -a + e - 1 >= 0 /\ -a - c + 4 >= 0 /\ c >= 0 /\ -a + c >= 0 /\ -a >= 0 ] (4, 1) f11(a, b, c, d, e, f) -> f11(a - 1, b, c, g, e, f) [ -f + 4 >= 0 /\ e - f + 3 >= 0 /\ c - f + 4 >= 0 /\ -a - f + 8 >= 0 /\ f - 4 >= 0 /\ e + f - 5 >= 0 /\ c + f - 4 >= 0 /\ -a + f >= 0 /\ e - 1 >= 0 /\ c + e - 1 >= 0 /\ -a + e + 3 >= 0 /\ -a - c + 4 >= 0 /\ c >= 0 /\ -a + c + 4 >= 0 /\ -a + 4 >= 0 /\ 0 >= g /\ a >= 1 /\ a >= b + 1 ] (4, 1) f11(a, b, c, d, e, f) -> f11(a - 1, b - 1, c + 1, g, e, f) [ -f + 4 >= 0 /\ e - f + 3 >= 0 /\ c - f + 4 >= 0 /\ -a - f + 8 >= 0 /\ f - 4 >= 0 /\ e + f - 5 >= 0 /\ c + f - 4 >= 0 /\ -a + f >= 0 /\ e - 1 >= 0 /\ c + e - 1 >= 0 /\ -a + e + 3 >= 0 /\ -a - c + 4 >= 0 /\ c >= 0 /\ -a + c + 4 >= 0 /\ -a + 4 >= 0 /\ a >= 1 /\ g >= 1 ] start location: f0 leaf cost: 1 By chaining the transition f11(a, b, c, d, e, f) -> f21(a, b, c, d, e, f) [ -f + 4 >= 0 /\ e - f + 3 >= 0 /\ c - f + 4 >= 0 /\ -a - f + 8 >= 0 /\ f - 4 >= 0 /\ e + f - 5 >= 0 /\ c + f - 4 >= 0 /\ -a + f >= 0 /\ e - 1 >= 0 /\ c + e - 1 >= 0 /\ -a + e + 3 >= 0 /\ -a - c + 4 >= 0 /\ c >= 0 /\ -a + c + 4 >= 0 /\ -a + 4 >= 0 /\ 0 >= a ] with all transitions in problem 5, the following new transition is obtained: f11(a, b, c, d, e, f) -> f21(a, b, c, d, e, f) [ -f + 4 >= 0 /\ e - f + 3 >= 0 /\ c - f + 4 >= 0 /\ -a - f + 8 >= 0 /\ f - 4 >= 0 /\ e + f - 5 >= 0 /\ c + f - 4 >= 0 /\ -a + f >= 0 /\ e - 1 >= 0 /\ c + e - 1 >= 0 /\ -a + e + 3 >= 0 /\ -a - c + 4 >= 0 /\ c >= 0 /\ -a + c + 4 >= 0 /\ -a + 4 >= 0 /\ 0 >= a /\ -a - f + 4 >= 0 /\ -a + f - 4 >= 0 /\ -a + e - 1 >= 0 /\ -a + c >= 0 /\ -a >= 0 ] We thus obtain the following problem: 6: T: (1, 2) f11(a, b, c, d, e, f) -> f21(a, b, c, d, e, f) [ -f + 4 >= 0 /\ e - f + 3 >= 0 /\ c - f + 4 >= 0 /\ -a - f + 8 >= 0 /\ f - 4 >= 0 /\ e + f - 5 >= 0 /\ c + f - 4 >= 0 /\ -a + f >= 0 /\ e - 1 >= 0 /\ c + e - 1 >= 0 /\ -a + e + 3 >= 0 /\ -a - c + 4 >= 0 /\ c >= 0 /\ -a + c + 4 >= 0 /\ -a + 4 >= 0 /\ 0 >= a /\ -a - f + 4 >= 0 /\ -a + f - 4 >= 0 /\ -a + e - 1 >= 0 /\ -a + c >= 0 /\ -a >= 0 ] (1, 1) f0(a, b, c, d, e, f) -> f11(4, g, 0, d, g, 4) [ g >= 1 ] (?, 1) f21(a, b, c, d, e, f) -> f21(a, b, c, d, e, f) [ -f + 4 >= 0 /\ e - f + 3 >= 0 /\ c - f + 4 >= 0 /\ -a - f + 4 >= 0 /\ f - 4 >= 0 /\ e + f - 5 >= 0 /\ c + f - 4 >= 0 /\ -a + f - 4 >= 0 /\ e - 1 >= 0 /\ c + e - 1 >= 0 /\ -a + e - 1 >= 0 /\ -a - c + 4 >= 0 /\ c >= 0 /\ -a + c >= 0 /\ -a >= 0 ] (4, 1) f11(a, b, c, d, e, f) -> f11(a - 1, b, c, g, e, f) [ -f + 4 >= 0 /\ e - f + 3 >= 0 /\ c - f + 4 >= 0 /\ -a - f + 8 >= 0 /\ f - 4 >= 0 /\ e + f - 5 >= 0 /\ c + f - 4 >= 0 /\ -a + f >= 0 /\ e - 1 >= 0 /\ c + e - 1 >= 0 /\ -a + e + 3 >= 0 /\ -a - c + 4 >= 0 /\ c >= 0 /\ -a + c + 4 >= 0 /\ -a + 4 >= 0 /\ 0 >= g /\ a >= 1 /\ a >= b + 1 ] (4, 1) f11(a, b, c, d, e, f) -> f11(a - 1, b - 1, c + 1, g, e, f) [ -f + 4 >= 0 /\ e - f + 3 >= 0 /\ c - f + 4 >= 0 /\ -a - f + 8 >= 0 /\ f - 4 >= 0 /\ e + f - 5 >= 0 /\ c + f - 4 >= 0 /\ -a + f >= 0 /\ e - 1 >= 0 /\ c + e - 1 >= 0 /\ -a + e + 3 >= 0 /\ -a - c + 4 >= 0 /\ c >= 0 /\ -a + c + 4 >= 0 /\ -a + 4 >= 0 /\ a >= 1 /\ g >= 1 ] start location: f0 leaf cost: 1 Complexity upper bound ? Time: 1.008 sec (SMT: 0.946 sec)